The antigen-binding fragment of human gamma immunoglobulin prevents amyloid β-peptide folding into β-sheet to form oligomers - Valls-Comamala, Victòria; Guivernau, Biuse; Bonet, Jaume; Puig, Marta; Perálvarez-Marín, Alex; Palomer, Ernest; Fernàndez-Busquets, Xavier; Altafaj, Xavier; Tajes, Marta; Puig-Pijoan, Albert; Vicente, Rubén; Oliva, Baldomero; et al. (Oncotarget, 2017)
The amyloid beta-peptide (Aβ) plays a leading role in Alzheimer's disease (AD) physiopathology. Even though monomeric forms of Aβ are harmless to cells, Aβ can aggregate into β-sheet oligomers and fibrils, which are both neurotoxic. Therefore, one of the main therapeutic approaches to cure or delay AD onset and progression is targeting Aβ aggregation. In the present study, we show that a pool of human gamma immunoglobulins (IgG) protected cortical neurons from the challenge with Aβ oligomers, as assayed by MTT reduction, caspase-3 activation and cytoskeleton integrity. In addition, we report the inhibitory effect of IgG on Aβ aggregation, as shown by Thioflavin T assay, size exclusion chromatography and atomic force microscopy. Similar results were obtained with Palivizumab, a human anti-sincitial virus antibody. In order to dissect the important domains, we cleaved the pool of human IgG with papain to obtain Fab and Fc fragments. Using these cleaved fragments, we functionally identified Fab as the immunoglobulin fragment inhibiting Aβ aggregation, a result that was further confirmed by an in silico structural model. Interestingly, bioinformatic tools show a highly conserved structure able to bind amyloid in the Fab region. Overall, our data strongly support the inhibitory effect of human IgG on Aβ aggregation and its neuroprotective role.